$I_λ$-Double statistical convergence of order $α$ in topological groups - Savaş, E. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We introduce а new notion, namely, $I_λ$-double statistical convergence of order α in topological groups. Consequently,we investigate some inclusion relations between $I$ -double statistical and $I_λ$ -double statistical convergence of order $α$ intopological groups. We also study many other related concepts.